Presence of Athletic Trainers in Michigan High Schools - Monica Lininger; Gayle Thompson (Bowling Green State University, 2015)
Context: Each year an estimated 1.4 million sports related injuries occur annually to student-athletes at the high school level. It has been over 20 years since a systematic investigation into the presence of athletic trainers to treat these injuries in the state of Michigan has been conducted. Within the past 5 years in Michigan, licensure as well as several laws and regulations have been enacted for athletic trainers. Purpose: To investigate the prevalence of athletic trainers in secondary schools in Michigan. Design: Cross-sectional study. Setting: Questionnaires were given to all 400 athletic directors in attendance of the Michigan Interscholastic Athletic Administrators Association (MIAAA) state conference. Participants: Seventy-eight athletic directors from Michigan high schools. Instrument: A seven item questionnaire was developed and pilot tested. Prevalence of athletic training services, the extent of coverage, the funding source of the athletic training services provided, and general characteristics of the school (size and setting type) were all assessed. Main Outcome measures: Descriptive statistics such as frequencies and medians were used along with Kendall's tau for test of association for nonparametric data. Results: Seventy-seven percent of those sampled indicated some form of athletic training services, and services tended to be more extensive at larger schools. Additionally, most (63%) of the athletic training services were funded from contracts with sports medicine clinics/hospitals. Coverage was mainly for practice and events (75%) with these services ranging from 26-40 hours per week at 42% of the schools in the sample. Conclusions: There has been a dramatic increase in the frequency of athletic training services in the high school setting in the state, but the level of coverage may not be adequate for all student-athletes.